Discourse as Social Representations: A Historical Perspective of Illicit Drugs in People’s Daily (1949–2016) - Tang, Qingye (Journal of drug issues, 2021)
This article draws on critical discourse analysis to examine how China’s mainstream newspaper People’s Daily represents illicit drugs from 1949 to 2016. The quantity of drug reports varies but has steadily increased with the severity of drug situations. Lexical variations show the prevalence of synthetic drugs and the newspaper’s major concern about drugs at different times. The diverse representations of drug types reveal the historical change in illicit drug use, production, and trafficking, and the rhetorical use of drug argots and metaphors disguises the outcomes of addiction and drug trade. The discursive variations in the reporting on illicit drugs are markedly conditioned by the social change and the domestic and global drug context and also reflect the evolution in China’s drug policies and attitudes toward drugs in society. The findings reveal the gradual shifts from the government’s strong ideological vigilance, concerns over Western imperialism, and the advocacy for strict law enforcement and draconian punishment to the people-oriented and public health approach.